Resilient Entrepreneurial Strategies Adopted by Zimbabwean Small and Medium Enterprises During Economic Crisis - Mufaro Dzingirai; Rodgers Ndava (IGI Global, 2022)
Resilient entrepreneurial strategy is a concept of great importance as it captures how entrepreneurs can ensure business sustainability in the face of harsh economic conditions of a market. In the wake of the economic crisis induced by the COVID-19 pandemic, it is not surprising to observe that scholars and practitioners are shifting their attention towards entrepreneurial resilience especially in the context of SMEs. With this in mind, this chapter focuses on the resilient entrepreneurial strategies adopted by Zimbabwean SMEs during the COVID-19 pandemic. The study established five strategies, namely strategic alliance, product differentiation, cost containment, innovation, and product differentiation. It is, therefore, recommended that SMEs should harness online technology and constantly re-evaluate entrepreneurial strategies in order to augment their agility to shocks emanating from the business environment.